Reproductive Health Education Management Based on Self-Care Module in the Pancasila Student Profile Strengthening Project - Yanti Rosmiyanti; Endang Komara; R Supyan Sauri; Waska Warta (Didaktika: Jurnal Kependidikan, 2025)
The background of this research is driven by the fact that many students have a limited understanding of the importance of maintaining reproductive health and making responsible decisions regarding reproductive behavior. This study aims to describe and analyze the management of reproductive health education based on the self-care module in implementing the Pancasila student profile strengthening project at Sehati Bina Insani IT Junior High School and Al Hasanat IT Junior High School. The approach used is qualitative with a case study method. Data collection techniques include observation, interviews, documentation studies, and data triangulation. The study results show that implementing reproductive health education management based on the self-care module in implementing the Pancasila student profile strengthening project in the two schools is effective. In conclusion, the implementation of the project to improve the profile of Pancasila students through reproductive health education based on self-care modules at Sehati Bina Insani IT Junior High School and Al Hasanat IT Junior High School showed significant success in the planning, organization, and implementation stages. The evaluation showed the effectiveness of this approach despite challenges related to limited resources, integration of Pancasila values, parental involvement, and teacher readiness. To overcome these challenges, the proposed solutions include improving the quality of resources, teacher training, collaboration with parents and the community, and using technology. It is hoped that this project can run optimally and positively impact students.